Potential use of two herbaceous forage (Axonopus catarinensis and Smallanthus sonchifolius) crops in the silvopastoral systems in the tropical highlands of Colombia - Lopera-Marín, Jhon Jairo; Angulo-Arizala, Joaquín; Murgueitio Restrepo, Enrique; Mahecha-Ledesma, Liliana (Agronomía Mesoamericana, 2023)
Introduction. Specialized dairy farming in Colombia highlands entails high production costs, methane emissions, nitrogen pollution in soil and water, the use of pesticides in pastures, and milk production that has not yet reached high-quality standards. All of these factors necessitate a structural change in the production model with a sustainability focus. In addition to other aspects, sustainable livestock farming requires greater complementarity and diversity of forage, shrub, and tree species adapted to high-altitude tropical conditions. Objective. To gather information through participatory action and rural innovation by producers and research advancements on the species Axonopus catarinensis and Smallanthus sonchifolius, herbaceous forage species with potential production and environmental benefits (in preliminary stage), for their integration into silvopastoral systems in the Colombian highlands. Development. A. catarinensis and S. sonchifolius are species that could be used in basic diet and energy supplementation, respectively, of dairy cows in the Colombian highlands. While there is no scientific information available for these conditions, some producers’ experiences suggest that these species may improve milk production and quality with positive effects on family economics. Additionally, they can contribute to the generation of dairy products with beneficial functional attributes that impact human health. Conclusion. A. catarinensis and S. sonchifolius are species that may have forage and nutritional potential to be included in silvopastoral dairy production systems in the Colombian highlands.